TEAMWORK AND DEDICATION - Moffitt, Brenda; Leonard, Regina (Operating Room Nurses Association of Canada Journal, 2007)
Brenda Moffitt and Regina Leonard were at their favourite spot (other than at work) – a quilt show – when the idea of making a Perioperative Services quilt was born. As caregivers, perioperative personnel are forever providing knowledge, skill, helping hands and hope to our patients. We wanted to have a medium through which to share our stories with others.